Curso on line em habilidades sociais para professores da pré-escola para inclusão de crianças com deficiência - Guimarães, Cristiane de Azevedo (2022)
Pre-school is a stage of schooling in which the child experiences major changes in their development, largely due to the social interactions established in the school context between peers and adults. Therefore, it is relevant to promote and expand the knowledge of Educational Social Skills of teachers who work in preschool, thinking about the promotion of inclusive education, as they play a fundamental role as mediators of knowledge and social interactions in the classroom. Thus, the general objective of the present study was to: Develop, apply and evaluate a training program on Social Skills and Educational Social Skills for preschool teachers. And the following specific objectives: a) Evaluate the teachers' knowledge in relation to HS concepts before and after the course; b) Describe teachers' socio-emotional strategies to promote interpersonal relationships in preschool; c) Analyze the pre-school teachers' HSE repertoire before and after the course; and d) Assess the social validity of the course. Thirty preschool teachers aged between 26 and 51 from different regions of the country participated. The course had a total duration of 60 hours, offered in three months, with a weekly frequency. Topics such as Special Education and school inclusion were considered, with discussions on social attitudes towards inclusion, educational beliefs, and current affairs, as well as the Teacher's Social Educational Skills to promote interactions and intentional learning with and between children, among others. The data were obtained from the application of: Registration form; Knowledge Questionnaire on Social Skills and Educational Social Skills; Questionnaire of Educational Social Skills for inclusion in everyday situations; Homework; Reflective Digital Narratives, and Social Validity Assessment of the Course. The data were analyzed qualitatively and quantitatively from the instruments used in the collection. Data from Google Forms were organized in Excel spreadsheets to calculate the initial and final scores of the student in the evaluations before and after the course. To compare the teachers' conceptual acquisition of Social Skills, statistical analysis was performed using the t-test. The procedural data collected during the course were evaluated according to the literature by content analysis and with the support of the IraMuTeq software. The results showed acquisition in relation to the participants' concepts related to Social Skills and Social Educational Skills. From a qualitative point of view, the teachers exposed in their teaching narratives the use of emotional self-control and self-knowledge promotion strategies, as well as delimiting the assertive, empathic communication and expressing solidarity Social Skills class as important to be exercised by the teacher in promoting inclusion of children with disabilities in preschool. In the social evaluation of the course, they pointed out the interactivity of the tasks and the use of discussion forums as tools that enriched the exchanges and enabled more learning. It is concluded that the course contributed to the conceptual formation of teachers in social skills and educational social skills and their relationship with the inclusion of children with disabilities, and the proposed course offered virtually met the learning expectations and proved effective in the assessment of course participants.